DIGITAL LEARNING SYSTEMS IN PUBLIC MIDDLE SCHOOLS: A COMPARATIVE STUDY OF TUNAS NUSA AND BLANGPIDIE 1 IN SOUTHWEST ACEH - Dewi, Feriana; Murniati AR; Qismullah Yusuf (RADJA PUBLIKA, 2024)
This study explores the management of IT-based learning at SMP Negeri Unggul Tunas Nusa and SMP Negeri 1 Blangpidie in Southwest Aceh Regency, focusing on the strategies employed in planning, implementation, evaluation, and overcoming challenges associated with integrating technology into educational practices. Through qualitative methods, including observations, interviews, and document analysis, the research unveils how both institutions have successfully navigated the complexities of incorporating IT into their curricula, highlighting the pivotal role of school leadership in fostering an environment conducive to digital learning. The findings reveal that strategic planning forms the cornerstone of effective IT-based learning, with both schools demonstrating comprehensive approaches to integrating technology through collaborative decision-making and program development. Implementation efforts have transformed the educational experience, making learning more engaging and interactive through the use of diverse technological tools and platforms. Continuous evaluation is emphasized to ensure the alignment of IT-based learning initiatives with educational objectives, enabling timely adjustments and optimizations. Despite the progress, challenges persist, including limited resources, varying levels of teacher IT proficiency, and inconsistent internet access, necessitating ongoing support, training, and infrastructural improvements. The study concludes that the deliberate and thoughtful management of IT-based learning at SMP Negeri Unggul Tunas Nusa and SMP Negeri 1 Blangpidie serves as a model for other educational institutions seeking to embrace the benefits of technology in education. The commitment to leveraging IT for enhancing teaching and learning processes underscores the potential of technology to revolutionize education, preparing students for the demands of the digital age.